The Centrosome Cell and Molecular Mechanisms of Functions and Dysfunctions in Disease - Schatten, Heide; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2012)
This book features a diversity of aspects on centrosome biology focused on the role of centrosomes in reproduction, cell and molecular biology of centrosomes, centrosome abnormalities in cancer, and centrosomes in various cell systems. Each section contains a variety of different subtopics written by experts in their respective fields who have contributed significant new knowledge to decipher structure and the multiple functions of this still intriguing central organelle. The chapters include comprehensive and concise reviews of key topics in the field as well as cell and molecular details that are important for the specific subtopics. Cutting edge new information is balanced with background information that is readily understandable for the newcomer and the experienced centrosome researcher alike. In addition, several articles will raise awareness of centrosomes in areas that have not yet considered centrosomes associated with disease including aspects of misguided signal transduction and several others that may find centrosomes as new targets for therapeutic intervention. The topics addressed are selected to be of interest to scientists, students, teachers, and to all who are interested in expanding their knowledge related to centrosomes. The book is intended for a large audience as a reference book on the subject.
Centriole Duplication and Inheritance in Drosophila melanogaster -- Sperm Centrioles and their Dual Role in Flagellogenesis and Cell Cycle of the Zygote Structure, Function and Pathology -- Centrosomal Functions and Dysfunctions in Cat Spermatozoa -- Nuclear-Centrosome Relationships During Fertilization, Cell Division, Embryo Development, and in Somatic Cell Nuclear Transfer (SCNT) Embryos -- Human Centrosomal Dynamics During Gametogenesis, Fertilization and Embryogenesis and its Impact on Fertility: Ultrastructure -- Asymmetric Centrosome Behavior in Stem Cell Divisions -- Functional Associations Between the Golgi Apparatus and the Centrosome in Mammalian Cells -- Many Pathways to Destruction: The Centrosome and its Control by and Role in Regulated Proteolysis -- Regulation of the Centrosome Cycle by Protein Degradation -- Molecular Links Between Centrosome Duplication and Other Cell Cycle Associated Events -- Regulation of Centrosomes by Cyclin-Dependent Kinases -- Disruption of Centrosome Duplication Control and Induction of Mitotic Instability by the High-Risk Human Papillomavirus Oncoproteins E6 and E7 -- Centrosomes, DNA Damage and Aneuploidy -- Centrosome Regulation and Breast Cancer -- The Role of Centrosomes in Multiple Myeloma -- Centrosomal Amplification and Related Abnormalities Induced by Nucleoside Analogs -- Mechanisms and Consequences of Centrosome Clustering in Cancer Cells -- Re-Evaluation of the Neuronal Centrosome as a Generator of Microtubules for Axons and Dendrites -- Centrosomes and Cell Division in Apicomplexa -- The Centrosome Life Story in Xenopus leavis -- Role of the MTOC in T cell Effector Functions -- Thoughts on Progress in the Centrosome Field.
Keywords: Life sciences; Cytology; Cell cycle; Life Sciences; Cell Biology; Cell Cycle Analysis; Cell Physiology